Risk of a second primary cancer after non-melanoma skin cancer in white men and women: a prospective cohort study. - Fengju Song; Abrar A Qureshi; Edward L Giovannucci; Charlie S Fuchs; Wendy Y Chen; Meir J Stampfer; Jiali Han (PLoS Medicine, 2013)
Previous studies suggest a positive association between history of non-melanoma skin cancer (NMSC) and risk of subsequent cancer at other sites. The purpose of this study is to prospectively examine the risk of primary cancer according to personal history of NMSC.In two large US cohorts, the Health Professionals Follow-up Study (HPFS) and the Nurses' Health Study (NHS), we prospectively investigated this association in self-identified white men and women. In the HPFS, we followed 46,237 men from June 1986 to June 2008 (833,496 person-years). In the NHS, we followed 107,339 women from June 1984 to June 2008 (2,116,178 person-years). We documented 29,447 incident cancer cases other than NMSC. Cox proportional hazard models were used to calculate relative risks (RRs) and 95% confidence intervals (CIs). A personal history of NMSC was significantly associated with a higher risk of other primary cancers excluding melanoma in men (RR=1.11; 95% CI 1.05-1.18), and in women (RR=1.20; 95% CI 1.15-1.25). Age-standardized absolute risk (AR) was 176 in men and 182 in women per 100,000 person-years. For individual cancer sites, after the Bonferroni correction for multiple comparisons (n=28), in men, a personal history of NMSC was significantly associated with an increased risk of melanoma (RR=1.99, AR=116 per 100,000 person-years). In women, a personal history of NMSC was significantly associated with an increased risk of breast (RR=1.19, AR=87 per 100,000 person-years), lung (RR=1.32, AR=22 per 100,000 person-years), and melanoma (RR=2.58, AR=79 per 100,000 person-years).This prospective study found a modestly increased risk of subsequent malignancies among individuals with a history of NMSC, specifically breast and lung cancer in women and melanoma in both men and women.